2010
DOI: 10.1111/j.1542-4774.2010.tb00544.x
|View full text |Cite
|
Sign up to set email alerts
|

How Important is Selection? Experimental VS. Non-Experimental Measures of the Income Gains from Migration

Abstract: Measuring the gain in income from migration is complicated by non-random selection of migrants from the general population, making it hard to obtain an appropriate comparison group of non-migrants. This paper uses a migrant lottery to overcome this problem, providing an experimental measure of the income gains from migration. New Zealand allows a quota of Tongans to immigrate each year with a lottery used to choose amongst the excess number of applicants. A unique survey conducted by the authors in these two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
129
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 322 publications
(134 citation statements)
references
References 30 publications
4
129
0
1
Order By: Relevance
“…A natural question is then how the individuals entering the PAC ballot differ from the general Tongan population. In other work (McKenzie et al 2010) we have shown that applicants to the PAC are positively selected in terms of education and prior earnings in Tonga, which is consistent with the positive self-selection of migrants on education worldwide (Grogger and Hanson, 2008). However, in Gibson et al (forthcoming) we show that there is no statistically significant self-selection in terms of either adult or child health.…”
Section: Contextsupporting
confidence: 86%
“…A natural question is then how the individuals entering the PAC ballot differ from the general Tongan population. In other work (McKenzie et al 2010) we have shown that applicants to the PAC are positively selected in terms of education and prior earnings in Tonga, which is consistent with the positive self-selection of migrants on education worldwide (Grogger and Hanson, 2008). However, in Gibson et al (forthcoming) we show that there is no statistically significant self-selection in terms of either adult or child health.…”
Section: Contextsupporting
confidence: 86%
“…In response to these concerns, scholars have employed several approaches, including randomized or quasi-randomized experiments and instrumental variables (Duncan et al 2007;Huston et al 2005;McKenzie et al 2010). A number of studies have used an instrumental variable (IV) that predicts the treatment variable but not the outcome variable, thereby mimicking random assignment (Antman 2008;McKenzie and Hildebrandt 2005).…”
Section: Selection and Causationmentioning
confidence: 98%
“…Over this issue, another compatible and consistent study that the role of migration towards the development of the economy is positive and encouraging (Crush and Frayne 2007). For evaluation purposes, simple comparisons give biased results and the choice of appropriate instrumental variable is the best way to deal this issue while difference-indifference approach and propensity score matching methods are also comparatively better (Mckenzie et al 2006). The use of 'Propensity Score Matching' is also emphasized in other studies as its use is increasing in policy evaluation community in scenarios where there is less control over the treatment group such as in observational studies (D'agostino 1998;Heinrich et al 2010).…”
Section: Introductionmentioning
confidence: 96%